Evaluating the Environmental and Economic Impacts of MARPOL Compliance in the Global Shipping Industry (Collaborate Engineering Daily Book Series, 2024)
The International Convention for the Prevention of Pollution from Ships (MARPOL) serves as a critical regulatory framework aimed at mitigating marine pollution caused by shipping activities. This study systematically evaluates the environmental and economic impacts of MARPOL compliance within the global shipping industry, focusing on its effectiveness in reducing pollution and enhancing sustainability. Utilizing a mixed-methods approach, we collected and analyzed quantitative data from a diverse sample of 50 shipping companies, alongside qualitative insights from industry experts and environmental reports. Our findings indicate a significant correlation between MARPOL compliance and a reduction in key environmental indicators, including a 30% decrease in oil spills and a 25% reduction in greenhouse gas emissions over the past decade. Moreover, while the initial compliance costs—averaging a 15% increase in operational expenses—pose challenges, the long-term economic benefits, such as a 20% increase in operational efficiency and enhanced market competitiveness, are noteworthy. The study underscores the necessity for ongoing regulatory support and financial incentives to facilitate compliance, particularly for smaller operators. Additionally, the research highlights the importance of continuous monitoring and adaptation of MARPOL regulations to address emerging environmental challenges, including the impacts of climate change. Ultimately, this study provides a comprehensive understanding of the dual impact of MARPOL compliance, presenting valuable insights for policymakers, industry stakeholders, and researchers aiming to foster a more sustainable shipping industry.
Keywords: MARPOL, environmental impact, economic impact, shipping industry, marine pollution